The Impact of Information and Communication Technologies on International Trade: The Case of MENA Countries - Kamel Touati; Ahmed Aljazea (Economies, 2023)
Given the importance of international trade, we empirically investigate the impact of information and communication technologies on the exports, imports, and total trade of five service items by using a panel data for 19 MENA countries from 2005 to 2019. Unlike most previous studies, we use the Information and Communication Technologies Development Index, which is a composite index that combines 11 indicators that include the access, use, and skill aspects of the technology. The results are as follows: the Information and Communication Technologies Development Index has a negative and statistically significant effect on exports of information technology services, and a positive and statistically significant effect on imports and total trade in financial services. Furthermore, we found also that the Information and Communication Technologies access sub-index has a significant effect on total trade in information technology services and transport. For the Information and Communication Technologies use sub-index, its effect on imports of travel services and exports of both travel and information technology services is significant. It also has a significant positive effect on total trade in travel and information technology services. As for the Information and Communication Technologies skills sub-index, the results show that it has significant positive effects on total trade in IT services and travel, and a negative significant effect on transport. These results provide interesting policy insights for information and communication technologies development and the growth of services trade for policy makers.